The use of Word Wall Learning Media in Science Learning to Improve The Learning Outcomes of Class 5c Students of Elementary School Kutowinangun 01 Salatiga - Andreas Paska Suryo Saputro; Adi Winanto (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Word walls are visual games that help students remember material easily, retain knowledge, and make learning fun. This research aims to improve student learning outcomes by implementing word walls in learning in class V. This research uses Classroom Action Research. The research informants consisted of 20 students of class V SD Kutowinangun 01 Salatiga, with details of 10 boys and 10 girls. Data collection techniques through observation and tests. The results of this research show an average score of 57.5% in the pre-cycle, far below the school's minimum standard of 75%. In the first cycle, student learning outcomes using the Word Wall approach showed improvement, but had not yet reached the minimum standard. The average student score increased from 61 in the 1st cycle 1 meeting test to 66.5 in the 2nd cycle 1st meeting learning outcomes. The number of students who got a score that reached the minimum standard was 60%, but the first cycle was considered not yet completed because the passing percentage had not yet reached 75%. In the second cycle, similar actions were carried out, and cycle 2 got better results. The average student score increased to 71 in the learning results of the 1st cycle 2 meeting test, but they still did not achieve success because only 60% of students passed. Finally, at the second meeting of the second cycle, the students' average score increased to 77%, meaning that the learning action using the word wall was successful and exceeded the minimum standard.